Comments and Illustrations of the European Federation of Societies for Ultrasound in Medicine Guidelines: Benign Pleura Lesions (Benign Pleura Thickening, Lesions and Masses)—What Can Be Seen on Transthoracic Ultrasound? - Kathleen Möller; Tomas Maruskin; Michael Ludwig; Wolfgang Blank; Stephan Eisenmann; Christian Jenssen; Hajo Findeisen; Burkhard Möller; Christoph F. Dietrich (Diagnostics)
Pleural thickening can be the result of inflammation or infection but can also have a neoplastic origin. Depending on the clinical context, a pleural lesion or mass is often initially suspected of malignancy. Benign pleural tumors are rare, and their appearance on ultrasound (US) is also described less frequently than pleural metastases or malignancies. There are few descriptions of contrast-enhanced Ultrasound (CEUS) in particular. This review introduces the basics of transthoracic ultrasound (TUS) of the pleura and CEUS of the pleura and lung. CEUS is recommended for pulmonary applications in the EFSUMB guidelines in non-hepatic applications. This article provides an overview of the characteristics of benign pleural thickening, tumor-like lesions, and benign pleural tumors on transthoracic B-mode US with color Doppler imaging (CDI) and CEUS. In detail, characteristics in TUS and CEUS are described for infectious/inflammatory pleural thickening (empyema, tuberculous pleuritis, hemothorax, fibrothorax), pleural thickening in various systemic diseases, in tumor-like conditions (plaques, splenosis, endometriosis, mesothelial cysts, lymphangiomatosis) and benign tumors (lipoma, benign SFT, schwannoma, solitary extramedullary/extraosseous plasmacytoma). The descriptions are illustrated by corresponding US and CEUS images.